Ebola virus disease and the 2026 FIFA World Cup mass gatherings: implications for global health security - Akinwumi A. Akinbodewa; Olumuyiwa E. Ariyo; Olorunfemi A. Ogundele; Oluwaferanmi M. Akinbodewa (International Journal Of Community Medicine And Public Health, 2026)
The 2026 Fédération Internationale de Football Association (FIFA) World Cup kicked off on June 11, 2026 in Mexico with the first opening match. It is unarguably the largest football event in the history of FIFA-organized tournaments, with three nations United States of America, Canada, and Mexico jointly hosting a 48-nation tournament featuring 104 matches. In contrast, previous tournaments, such as the 2022 event in Qatar, were limited to 32 participating countries and a single host nation. The number of participating countries from Africa was raised from five to nine with the epicentre of the current Ebola virus disease (EVD) outbreak, DR Congo (DRC) one of the participating countries having qualified through the intercontinental play off. Equally important is the fact that it is the longest running World Cup event lasting 39 days compared to 32 days previously.